(untitled) (American Journal of Agricultural Science, Engineering, and Technology, 2024)
Feed additives are given to broiler diets to boost productivity and growth rate. Ginger and garlic have acquired popularity for increasing the health and nutritional value of poultry products. This study aims to evaluate how dietary supplementation with garlic and ginger powder, as well as their combination, affects broiler feed intake and growth performance. Arbor acres chicks, 180 days old, were randomly assigned to five treatments with three replicates (12 birds each). Treatment 1 was a diet without ginger or garlic (control). Treatments 2 and 3 included 0.25% of ginger and garlic, respectively. Treatments 4 and 5 contained 0.25% and 0.50% ginger and garlic, respectively. The feeding experiment was conducted for 42 days. During the beginning phase, birds fed a combination of 0.25% ginger and garlic showed significantly higher weekly weight gain (84.22g/bird) and daily weight gain (12.03g/bird) compared to other treatments. Birds fed with 0.25% ginger exhibited the highest feed intake throughout both the starter and finisher phases (20.84g/bird and 54.79g/bird, respectively). Birds fed 0.25% ginger and garlic exhibited considerably higher feed conversion ratios (p<0.05) throughout both the starter and finisher phases. Therefore, it can be inferred that ginger and garlic at the inclusion rate of 0.25% ginger, 0.25% garlic, and 0.25% garlic in combination with 0.25% ginger can improve the feed intake and weight gain of broilers.